Investigations of air-water multiphase flow in tubes: Computational fluid dynamics / Goo Wei Hong - Goo, Wei Hong (2020)
Mixing is a very crucial process in many industries, such as food processing industry, minerals processing industry, petrochemicals and refining industry, pulp and paper industry, polymer industry, pharmaceuticals industry and many more. There are different types of mixing, such as liquid-gas mixing, liquid-liquid mixing, solid-liquid mixing and many more. The definition of multiphase flow is the simultaneous flow of materials with multiple thermodynamic phases. A lot of process industries require multiphase flows during operation. Bubbly flow is defined as the flow of liquids that contains dispersed gas bubbles. One of the main applications of multiphases flows and bubbly flows is static mixer. The experimental and simulation studies on multiphase flows, especially bubbly flows are not widely performed due to due to several constraints. Therefore, the focus of this research project is on investigating bubbly flow using Computational Fluid Dynamics (CFD) software. The three most common multiphase models in FLUENT are Volume of Fluid (VOF) model, Mixture model and Eulerian model. The two most common models under Eulerian multiphase model in simulating bubbly flow are Population Balance Model (PBM) and Interfacial Area Concentration (IAC) model. The PBM and IAC model are compared with an available case study from ANSYS in simulating bubbly flow in a 2D vertical bubble column reactor. It is found that the simulation results obtained using PBM compared to IAC model, such as air volume fraction contours, water velocity vectors, air bin 0 fraction contours, graphs of air bin 3 fraction versus X direction at the centre of the 2D vertical bubble column reactor, discrete size 3 fraction of air contours, Sauter mean diameter of air contours and Sauter mean diameter distribution of air histograms have higher similarity with the results from the case study, but there exist some differences between the results. Not only that, the bubbly iv flow in 2D horizontal pipe is studied by manipulating the ratio of air velocity to water velocity (AV/WV) using PBM. It is found that the air volume fraction in the 2D horizontal pipe decreases when the AV/WV ratio decreases from 1. It is found that the air bubbles migrate towards the top wall of the 2D horizontal pipe almost instantly when the ratio of AV/WV is higher than 1 due to the larger buoyancy force whereas the air bubbles tend to travel the furthest at the centre of the 2D horizontal pipe before migrating to the top wall when the ratio of AV/WV is 1. However, the distance the air bubbles travel at the centre of the 2D horizontal pipe reduces if the AV/WV ratio decreases from 1. Lastly, CFD simulation of air-water multiphase flow in 3D Kenics static mixer is performed using VOF multiphase model by manipulating the volume fraction of air at the inlet. It is found that the mixing characteristics of the 3D Kenics static mixer are almost similar for the different volume fractions of air at the air inlet. However, reversed flow of water occurs due to the pressure-outlet boundary conditions at the outlets.